Debating threats: fear in Spanish political election propaganda - Sara Rebollo-Bueno (Cuadernos.info)
This study examines the use of fear by Spanish political parties in electoral debates since the collapse of traditional bipartisanship in 2014. The decision to use fear is due to the recent turbulent events that Spain has experienced politically and socially since new political parties emerged. Using content analysis and critical discourse analysis, this study examines how fear is used in the typical propaganda format of debates involving fewer intermediaries. Five debates from the parliamentary elections since 2014 in which more than two presidential candidates participated (446 interventions in total) are examined. Thus, the threats alluded to by the different parties, the propaganda techniques used and the themes that take center stage in the speeches when it comes to generating fear are identified. In this way, it is established that the parties use fear differently depending on their ideology and that their age or tradition is a secondary variable.